Development of an Algorithm for Sizing Storage Systems for Rainwater Harvesting - Panu, U. S.; Rebneris, R. J.; Sharma, T. C. (Africa Environmental Review Journal, 2015)
This paper investigates the potential of a Rain Water Catchment System (RWCS) for meeting and/or supplementing the irrigation requirements for urban residential landscapes in a Canadian situation. In a specific usage of harvested rainwater for irrigation the urban landscape, the determination of the potential landscape area is best achieved through the spreadsheet-based water balance studies. Such computer based water balance programs invoke recursive approach to maximize the landscape area that can be irrigated by the rainwater catchment system by setting the design rainfall at a desired probability level, preferably at 50% (median value). The methodology developed in this paper was applied to size the rainwater storage systems for the city of Thunder Bay, Canada. The median roof catchment area was determined as 120 m2 and the capacity of an optimal RWCS was found to be approximately 1500 litres i.e., three tanks of 500 litres each that are commonly available in the market.